Endocrinal metabolic regulation on the skeletal system in post-menopausal women - Thapa, Santosh; Nandy, Ananya; Rendina-Ruedy, Elizabeth (Frontiers in Physiology, 2022)
Osteoporosis is a common endocrinologic disorder characterized as a chronic bone loss condition. Sexual dimorphism is ubiquitous in the incidence of osteoporosis with post-menopausal women being acutely affected. Gonadal sex hormones including estrogen act as crucial regulators of bone mass; therefore, loss of such hormones leads to an imbalance in skeletal turnover leading to osteoporosis. Estrogen can influence both bone formation as well as resorption by reducing osteoblast activity and enhancing osteoclastogenesis. Additionally, estrogen is a potent regulator of systemic metabolism. Recent studies have provided clues that estrogenic effect on bone might also involve alterations in bone cell metabolism and bioenergetic potential. While direct effects of gonadal hormones ability to alter intracellular metabolism of bone cells has not been studied, there is precedence within the literature that this is occurring and contributing to post-menopausal bone loss. This review aims to serve as a perspective piece detailing the prospective role of gonadal hormones regulating bone cell metabolic potential.